Environmental Crisis: Islamic Ecoteology, Green Science, and Sustainability - Fajar Aswati; Isri Nasifah; Haris Riadi (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the environmental crisis through the lenses of Islamic ecotheology, green science principles, and sustainability strategies. The approach seeks to offer a holistic solution that integrates spiritual values, environmental ethics, and eco-friendly scientific practices. The method employed is a comprehensive literature review and qualitative analysis, examining Islamic ecotheology, green science theories, and contemporary sustainability policies. The findings indicate that Islamic ecotheology emphasizes human responsibility as stewards of the Earth, promoting conservation ethics and ecological justice; green science provides a technical framework for efficient resource management with minimal environmental impact; while sustainability acts as an integrative bridge between spiritual principles and scientific practices, highlighting social, economic, and ecological continuity. The study implies the need for environmental education grounded in Islamic values, green technological innovation, and policies supporting collaboration among communities, scientists, and governments to mitigate environmental crises sustainably.